2016
DOI: 10.1111/jpm.12330
|View full text |Cite
|
Sign up to set email alerts
|

Factor affecting happiness among nursing students in South Korea

Abstract: Introduction Happiness is very important in the training and development of nursing students as future nurses. However, nursing students experience a high level of stress and low level of happiness in South Korea. Aim This study aimed to investigate factors that affect happiness among nursing students in South Korea. Method Data were collected from a total of 241 nursing enrolled in two 4-year baccalaureate nursing programmes in South Korea, using a self-administrated questionnaire. To identify predictors of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 38 publications
2
35
1
Order By: Relevance
“…This seems to be similar to previous studies that major satisfaction affects positive emotions such as happiness of subjects. 16,17 In addition, based on the results of this study, which showed that the degree of major satisfaction was negatively correlated with the clinical practice stress, and that it was positively correlated with the clinical practice stress, it is estimated that gratitude, which is one of the factors of positive strength, 36 mediates major satisfaction and clinical practice satisfaction. Therefore, it will be important to develop a program for improving dispositional gratitude that includes consistent counselling management on major satisfaction.…”
Section: Factors Affecting Satisfaction With Clinical Practicementioning
confidence: 86%
See 1 more Smart Citation
“…This seems to be similar to previous studies that major satisfaction affects positive emotions such as happiness of subjects. 16,17 In addition, based on the results of this study, which showed that the degree of major satisfaction was negatively correlated with the clinical practice stress, and that it was positively correlated with the clinical practice stress, it is estimated that gratitude, which is one of the factors of positive strength, 36 mediates major satisfaction and clinical practice satisfaction. Therefore, it will be important to develop a program for improving dispositional gratitude that includes consistent counselling management on major satisfaction.…”
Section: Factors Affecting Satisfaction With Clinical Practicementioning
confidence: 86%
“…Recent empirical evidence has accumulated that gratitude contributes to people's health and ability to adapt, with much research reporting that people with stronger disposition of gratitude enjoy greater wellness and happiness, exhibit more pro-social behaviours, and have lower levels of stress and depression. [15][16][17][18][19][20] Based on previous studies, we can presume that gratitude has the potential to positively affect stress situations, such as clinical practice, that nursing students confront. 21 Yet research on the relationship between clinical practice stress and a disposition of gratitude in nursing students is hard to find.…”
mentioning
confidence: 99%
“…For this reason, there are many university students in Korea who choose their majors without considering their aptitudes. Therefore, many who choose nursing because of parents' recommendations or guaranteed employment face ambivalence in regard to their career, which can lead to dropping out of the program or resigning from their nursing jobs [34].…”
Section: Discussionmentioning
confidence: 99%
“…Such approaches should consider the factors that enhance nurse's work psychological inspiration, happiness and nurses' recognition of their influence on work. [3,4,13,15] 1.1 Aim and significance Hospitals in Saudi Arabia have suffered from nurses scarcity and their work leave or absenteeism. Considering nurses' perception of their influence on work and their happiness is an important role of the nurse manager.…”
Section: Introductionmentioning
confidence: 99%